2014
DOI: 10.1001/virtualmentor.2014.16.12.pfor1-1412
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine: Innovation Has Outpaced Policy

Abstract: Digital-age technology offers great promise for improving access to and quality of health care via transformational care delivery mechanisms. Demand for innovative solutions has been driven by an aging population, high rates of chronic illness, geographic and sociodemographic disparities in access to care, and increasing numbers of insured Americans seeking care in the face of health professional workforce shortages; the AAMC recently projected an estimated shortage of 46,000 primary care clinicians and 45,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, one key finding is that telehealth has become a necessity, not just a convenience (88). The scale of the systemic changes required for its deployment has shown that technology "has outpaced policy" (113). The crisis has highlighted the gap between the obsolete and/or incoherent regulatory, economic, organizational, legal, technological, and clinical-administrative frameworks still in use in the HSSS and the requirements for innovative models of care and service delivery.…”
Section: Implications For the Future And Conclusionmentioning
confidence: 99%
“…However, one key finding is that telehealth has become a necessity, not just a convenience (88). The scale of the systemic changes required for its deployment has shown that technology "has outpaced policy" (113). The crisis has highlighted the gap between the obsolete and/or incoherent regulatory, economic, organizational, legal, technological, and clinical-administrative frameworks still in use in the HSSS and the requirements for innovative models of care and service delivery.…”
Section: Implications For the Future And Conclusionmentioning
confidence: 99%
“…An increasingly developed base of knowledge around CH and CH practices has generated many definitions of exactly what CH is [2,8]. For instance, the American Medical Association (AMA) defines CH as a model that utilizes technology to maximize health care resources and offer enhanced, flexible opportunities for patients to engage with clinicians and better self-manage their care [9]. In order to achieve these goals, many technologies, including telemedicine and mobile health, are used to facilitate remote, mobile, and site-to-site medical care.…”
Section: Definition Of Connected Healthmentioning
confidence: 99%
“…Remote medical care is a key feature of CH [3][4][5][9][10][11][12]. Studies indicate that both the concept of remote health care and the practical application of information technology systems to health care include aspects of remote medical care, such as a telecare medicine information system, a personally controlled health records system, and patient monitoring.…”
Section: Remote Health Carementioning
confidence: 99%